Cambodia’s hedging foreign policy between the United States and China: the role of domestic politics, 1999-2019 - Chansambath, Bong (Kansas State University, 2020)
The rise of the People’s Republic of China (PRC) and the apparent transition from the post Cold War unipolarity to multipolarity of the twentieth-first century have resulted in a highly fluid geostrategic environment in the Asia-Pacific region, where signs of potential aggressors are not clear cut, and structural power among major states still unfolds with considerable uncertainty. This condition inclines small states such as Cambodia to reject traditional bandwagoning and balancing schools of thought that require them to choose a side between contesting big powers. Instead, they opt for a pragmatic foreign policy known as “hedging” by forging relations with multiple external players concurrently. Through the lens of survival of authoritarian regimes, this qualitative study contends that Cambodia’s general election cycle influences its hedging between the United States and the PRC from 1999 to 2019. On the one hand, Cambodia’s economic and military relations with the United States remain stable and mature over time, whereas its political ties deteriorate temporarily during elections because of government repression. On the other hand, Cambodia’s relations with China deepen without fluctuation regardless of electoral cycles. The ultimate goal of this strategy is to uphold the legitimacy of the ruling Cambodian People’s Party (CPP) by retaining the support of two key constituencies in Cambodian politics: the winning coalition and the opposition group. This study concluded that Cambodia hedged by engaging not only with the United States and China but also with Japan, the European Union, and the Association of Southeast Asian Nations (ASEAN) in order to bolster economic growth, maintain internal stability, strengthen its armed forces, preserve the regional balance of power, and project an ambivalent image of its alignment posture. The thesis offers policy implications for the scholarship on the foreign policy of small autocratic states and the future of U.S. foreign policy in Asia.
Keywords: Cambodia; Cambodian People's Party; Hedging; Foreign policy; United States-Cambodian relations; Chinese-Cambodian relations